Continuous Cloud-Scale Query Optimization and Processing - Bruno, Nicolas; Jain, Sapna; Zhou, Jingren (Proc. VLDB Endow., 2013)
Massive data analysis in cloud-scale data centers plays a crucial role in making critical business decisions. High-level scripting languages free developers from understanding various system trade-offs, but introduce new challenges for query optimization. One key optimization challenge is missing accurate data statistics, typically due to massive data volumes and their distributed nature, complex computation logic, and frequent usage of user-defined functions. In this paper we propose novel techniques to adapt query processing in the Scope system, the cloud-scale computation environment in Microsoft Online Services. We continuously monitor query execution, collect actual runtime statistics, and adapt parallel execution plans as the query executes. We discuss similarities and differences between our approach and alternatives proposed in the context of traditional centralized systems. Experiments on large-scale Scope production clusters show that the proposed techniques systematically solve the challenge of missing/inaccurate data statistics, detect and resolve partition skew and plan structure, and improve query latency by a few folds for real workloads. Although we focus on optimizing high-level languages, the same ideas are also applicable for MapReduce systems.